2010
DOI: 10.1002/jclp.20659
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to psychological treatments and their relationship to depression

Abstract: In spite of repeated calls for research and interventions to overcome individual and systemic barriers to psychological treatments, little is known about the nature of these barriers. To develop a measure of perceived barriers to psychological treatment (PBPT), items derived from 260 participants were administered to 658 primary care patients. Exploratory factor analysis on half the sample resulted in 8 factors, which were supported by confirmatory factor analysis conducted on the other half. Associations gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
249
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 308 publications
(260 citation statements)
references
References 28 publications
7
249
2
2
Order By: Relevance
“…Analysis of individual items revealed that participants did, however, report that computer-based treatment had advantages such as reduced cost, being easier to access, and flexibility in meeting individual needs. This finding is similar to other studies in which participants reported perceiving advantages to internet-based treatment but expressed an overall preference for face-to-face treatment (Mohr et al, 2010).…”
Section: Attitudes To E-mental Health Servicessupporting
confidence: 90%
“…Analysis of individual items revealed that participants did, however, report that computer-based treatment had advantages such as reduced cost, being easier to access, and flexibility in meeting individual needs. This finding is similar to other studies in which participants reported perceiving advantages to internet-based treatment but expressed an overall preference for face-to-face treatment (Mohr et al, 2010).…”
Section: Attitudes To E-mental Health Servicessupporting
confidence: 90%
“…Future studies investigating the efficacy of self-help interventions for psychosis might, therefore, usefully consider rates of uptake and engagement, along with strategies that might promote uptake. Self-help interventions overcome many of the practical barriers that are associated with face-to-face therapies including the costs of therapy, transportation difficulties and issues with childcare or caring for sick or disabled loved ones (Mohr, Hart, & Howard, 2006;Mohr et al, 2010). However, P r e P u b l i c a t i o n C o p y one potential barrier to the uptake of interventions (likely including self-help interventions for psychosis) is the stigma associated with mental health (Barney, Griffiths, Jorm, & Christensen, 2006;Corrigan, Larson, & Rusch, 2009;Schomerus & Angermeyer, 2008;Tanskanen et al, 2011;Vogel, Wade, & Hackler, 2007).…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Research also suggests that two thirds of clients with depression hold a preference for psychological interventions over pharmacological solutions [6]. However, accessing evidence-based psychological interventions can be difficult because of a number of barriers [7,8], including not having access to treatment due to a lack of health service resources [7]. These barriers can be more pronounced for severe depression [9] and most individuals with severe levels of depression do not receive adequate treatment [10].…”
Section: Treatment For Depressionmentioning
confidence: 99%